A COVID-19 call center for healthcare providers: dealing with rapidly evolving health policy guidelines - Aharona Glatman-Freedman (Israel Journal of Health Policy Research, 2020)
Abstract Background Communication between health authorities and healthcare providers is an essential element of the response to public health emergencies. Although call centers can facilitate such communication, no published reports describing their outcomes exist. In advance of the expected COVID-19 outbreak in Israel, the Israel Center for Disease Control established a call center dedicated to queries from healthcare professionals. Methods The call center operated from February 5, 2020 (week 6) to May 14, 2020 (week 20). Data on calls received, including date and time, caller characteristics, questions and responses were recorded in a database designed for this purpose. The volume, sources and content of queries were analyzed. Results In 15 weeks of operation, the call center responded to 6623 calls. The daily number of calls ranged from 1 to 371 (mean 79.8, median 40), peaking on week 12, 2 weeks prior to a peak in new COVID-19 cases. Callers were predominantly physicians (62.4%), nurses (18.7%) and administrators (4.4%). Most worked in primary care clinics (74.2%) or hospitals (8.7%). Among physicians, 42.3% were family physicians or internists, and 10.0% were pediatricians. The issues most commonly addressed were home quarantine (21.6%), criteria for suspected cases (20.6%), and SARS-CoV2 testing (14.1%). Twenty-five percent of questions involved requests for clarifications of MOH guidelines regarding travel restrictions, clinic management, triage of symptomatic patients, routine medical and dental care, recommended precautions for health care workers with preexisting medical conditions, and other matters. A total of 119 queries were not resolved on the basis of existing guidelines and were referred to MOH headquarters. Conclusions This is the first report of a call center established to serve the needs of healthcare providers seeking guidance on COVID-19 management, and to facilitate communication of providers’ concerns to the central health authority. Our work indicates that a central call center for healthcare providers can facilitate the development, implementation and amendment of guidelines and should be an integral element of the early response to public health emergencies. Real-time analysis of the call data may reveal important trends requiring prompt attention.